(3JfbjM cJGH GdJMbjb aj CMGOjK GdJYdjbs - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s; (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL,J (B597 (3g` s
(3ChdgG (B:s
(3jHOC HeSGFd ai GdWgGQI s
(3BNQgG (B:s
(3Ge GdhdO dGjLhR HjYgG NdGa dOGhO Cf GdfHi Udi Gddg Ydjg hSde fgi Yf HjY GegGJ GdChdGO hbGd dGJHYf hdG Jgf bGd YHjOI aQCjJ Ydi hYeQ GdLeGYI GMH Edi eQGOi Ydi hMOg Je GdcJGH s
(3GdfSNI HgG MhGTs
(3Ydjg JhbjYGJ Ydi Hf YHO GdcGai GdSHci SfI (B749 (3g` hUdGM GdOjf GdUaOi SfI (B735 (3g` GdPi CbQCg ai efRd GdPgHis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdMOjK h GdeUWdMs